2003
DOI: 10.21273/jashs.128.5.0761
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat or 1-Methylcyclopropene on Antioxidative Enzyme Activities and Antioxidants in Apples in Relation to Superficial Scald Development

Abstract: `Granny Smith' apples [Malus sylvestris (L.) Mill. var. domestica (Borkh.) Mansf.] were harvested in two seasons and stored at 0 °C air storage with no pretreatment (control), after heating for 4 d at 38 °C, or after treating for 16 hours at 20 °C with 1 μL·L-1 1-methylcyclopropene (1-MCP). The effects of the two treatments on superficial scald development were consistent over both seasons. Scald began to appear after 8 weeks in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
26
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 34 publications
6
26
0
2
Order By: Relevance
“…The very low ethylene production in LO2‐treated fruits during the first 3 months of cold storage at 0 °C is consistent with results obtained with avocados treated with LO2 for 24 h prior to cold storage,34 and with our previous results with Granny Smith apples that were pretreated with LO2 for 7 days at 20 °C 12. The inhibition by LO2 treatment of ethylene production during subsequent cold storage was similar to the inhibition by 1‐MCP that was described in previous reports 4, 9, 35. However, in LO2‐treated fruits there was a burst of ethylene production when the fruits were transferred to 20 °C, whereas this did not occur in 1‐MCP‐treated fruits (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The very low ethylene production in LO2‐treated fruits during the first 3 months of cold storage at 0 °C is consistent with results obtained with avocados treated with LO2 for 24 h prior to cold storage,34 and with our previous results with Granny Smith apples that were pretreated with LO2 for 7 days at 20 °C 12. The inhibition by LO2 treatment of ethylene production during subsequent cold storage was similar to the inhibition by 1‐MCP that was described in previous reports 4, 9, 35. However, in LO2‐treated fruits there was a burst of ethylene production when the fruits were transferred to 20 °C, whereas this did not occur in 1‐MCP‐treated fruits (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The effect of 1-MCP content has been investigated by Larrigaudière et al (2004) who reported an increase in the enzymatic antioxidant capacity following 1-MCP treatment in 'Blanquilla' pears, and interpreted it as a sign of a general metabolic change influenced by ethylene. In contrast, Shaham et al (2003) observed low activities of most antioxidant enzymes in 1-MCP treated 'Granny Smith' apples. In this study, no clear effect of treatment on phenols or antioxidant activity can be attributed to 1-MCP.…”
Section: Ripening Behavior After Storagementioning
confidence: 70%
“…The same positive effect was also noted under CA, though at lower levels. One of the positive results obtained in the studies carried out with different apple cultivars on the efficacy of 1-MCP is the reduction in the ISS and SSS (Watkins et al 2000;Deell et al 2002;Johnson 2003;Shaham et al 2003;Zanella 2003). the PRF in 1-MCP + NA at quite lower levels compared with NA alone at the end of shelf life.…”
Section: Iss and Sssmentioning
confidence: 99%